2022
DOI: 10.1177/15347346211065929
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Recurrent Venous Ulcer in Patients Treated at an Outpatient Clinic: Historical Cohort

Abstract: The recurrence of venous ulcers is the wound reopening after a period of completed epithelisation of a previous ulcer due to exposure to causal factors and lack of prevention. Venous ulcers have a high recurrence rate that may increase through the years. Epidemiological evidence on its incidence and risk factors is scarce due to the lack of patient follow-up in outpatient clinics and adherence to treatment after healing. The objective was to analyze the incidence of venous ulcers recurrency in outpatients and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
4
0
2
Order By: Relevance
“…In an observational historical cohort carried out at a stomatherapy center in the city of São Paulo, it was revealed that recurrent VUs in the legs were identified mainly in women aged 60 years or older, obese, hypertensive and diabetic; the incidence of recurrence of VUs in the legs of patients with this profile identified in an outpatient clinic is 48.5%. Another critical factor in the results demonstrated that obesity increased by 8.7 times the chances of patients with healed ulcers having an ulcer recurrence 24 .…”
Section: Discussionmentioning
confidence: 93%
“…In an observational historical cohort carried out at a stomatherapy center in the city of São Paulo, it was revealed that recurrent VUs in the legs were identified mainly in women aged 60 years or older, obese, hypertensive and diabetic; the incidence of recurrence of VUs in the legs of patients with this profile identified in an outpatient clinic is 48.5%. Another critical factor in the results demonstrated that obesity increased by 8.7 times the chances of patients with healed ulcers having an ulcer recurrence 24 .…”
Section: Discussionmentioning
confidence: 93%
“…Common risk factors for VLU occurrence, such as the female gender, being elderly, and having obesity, also seem to be involved in recurrence occurrence. For example, obesity increases, by 8.7 times, the risk of recurrence [ 14 ]. Also, some comorbidities, such as systemic arterial hypertension, can bring an additional risk.…”
Section: Discussionmentioning
confidence: 99%
“…Em coorte histórica observacional realizada em um centro de estomaterapia na cidade de São Paulo, revelou-se que as UVs recorrentes nas pernas foram identificadas principalmente em mulheres com 60 anos ou mais, obesas, hipertensas e diabéticas; é de 48,5% a incidência de recorrência de UVs nas pernas de pacientes com esse perfil identificados em ambulatório. Outro fator importante nos resultados demonstrou que a obesidade aumentou em 8,7 vezes as chances de os pacientes com úlceras curadas terem uma recorrência da úlcera 24 .…”
Section: Discussionunclassified